Construction Control Technology and Monitoring Analysis of Walking Incremental Launching Construction of Small-Curvature Steel Box Girder Bridges Across Expressways - Hai Huang; Xiaomin Xue; Haitao Ma; Zhijun Zhou; Jianbo Dou; Heng Yang; Erwei Guo; Jianjun Ma (Applied Sciences)
As urban areas keep growing, there are higher requirements for the carrying capacity of traffic operations, and there are more and more curve incremental launching projects with complex construction conditions. This paper builds upon the walking incremental launching project of a small-curvature steel box girder in Xuchang City and has developed a detailed construction method and monitoring technology. Due to the bridge’s longitudinal gradient being designed as a two-way slope and falling under the category of a small-radius steel box girder, the front end of the main beam exhibits significant lateral deviation, and linear control is difficult. It is necessary to carry out stress and displacement monitoring of the whole process of construction of the curved steel box girder and the guide girder to guide the construction process. The stress conditions of the incremental launching pier and the settlement of the concrete substructure are also studied, and we analyze the stress and displacement characteristics. Firstly, the finite element tool MIDAS Civil is adopted to build a model for the construction. The five most unfavorable working conditions are selected from the entire incremental launch process to analyze the internal force and displacement state of the steel box girder bridge, which is and then compared with the site monitoring value. It is demonstrated by the outcomes that the internal force and deflection of the steel box girder and the guide girder are within the safe construction range, which ensures the security of the incremental launching construction. In the maximum cantilever condition, the guide girder experiences significant stress, but the maximum value is not observed during the maximum cantilever condition of the guide girder. Therefore, whole-process monitoring should be carried during construction to maintain safety measures and quality management.